2019
DOI: 10.25289/ml.2019.8.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a 1,064 nm Microlens Array-type, Picosecond-dominant Laser for Pigmented Scars with Improvement of Vancouver Scar Scale

Abstract: Background and ObjectivesThe picosecond 755 nm alexandrite laser was first approved by the US FDA in 2012. A previous study described the use of a 1,064 nm picosecond laser with a micro-lens array (MLA) in peri-areolar scarring from breast reconstruction surgery and reported significant improvement in the texture and aesthetic appearance of the scar without other wound complications. The purpose of this study was to evaluate the improvement of overall scarring, not just pigmentation, in the picosecond laser tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Second, this study used VSS, a widely accepted and validated tool for measuring scar affinity, to evaluate scars. VSS has been used in many studies because it is a reliable and useful tool for scar assessment [ 34 , 35 , 36 ]. Third, another advantage of this study is that the relationship between the collagen type I/III ratio and scar formation could be understood in more detail by using multiple linear regression analysis to identify the factors affecting scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study used VSS, a widely accepted and validated tool for measuring scar affinity, to evaluate scars. VSS has been used in many studies because it is a reliable and useful tool for scar assessment [ 34 , 35 , 36 ]. Third, another advantage of this study is that the relationship between the collagen type I/III ratio and scar formation could be understood in more detail by using multiple linear regression analysis to identify the factors affecting scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Picosecond laser with MLA pulses concentrate enough power in targeted spots to generate LIOB either in the epidermis or the dermis. 5,6 Laser-induced optical breakdown is different from other laser-based method that it's a non-linear absorption process only can occur when the radiance is high enough to produce a critical free electron density of 10 21 cm -3 . Free electrons around targeted area absorb laser light and form second free electrons.…”
Section: Discussionmentioning
confidence: 99%
“…In the last step of LIOB, plasma generation inducing explosive vaporization occurs. 6,7 It makes cavitation bubbles in the skin. These bubbles expand and disrupt tissues around and generate shock waves that last disruption of tissue and generate repair.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we also reported on the usefulness of treatment for depressed or pigmented scars through 1,064-nm Nd:YAG picosecond laser with micro-lens array (MLA). 3,4 There are several studies comparing the two treatments, but there is no study that combined the two treatments. 5 In this study, after several fractional CO2 laser treatment sessions, we tried to see if additional picosecond laser was effective on facial scars.…”
Section: Introductionmentioning
confidence: 99%